Deciphering Th-Related Gene Interactions in Chronic Spontaneous Urticaria: Bioinformatics Insights and Drug Affinity Exploration - Deepika . (International Journal of Genetic Modifications and Recombinations, 2024)
Objective: There has been a great deal of interest in how inflammatory dermatosis and The cell interact, but the etiopathogenesis of chronic spontaneous urticaria (CSU) is still inadequately comprehended. Through bioinformatics techniques, the purpose of this work is to elucdate the molecular mechanism underlying Th-related genes in CSU and seeks to find the highest affinity drug. Methods: The CSU RNA expression profiling dataset provided the basis for the investigation. The analysis included differentially expressed Th cell-related genes (DEThRGs), gene ontology (GO), kyoto encyclopedia of genes and genomes (KEGG), and Disease Ontology (DO). Using protein-protein interaction analysis, the hub genes were investigated. Additionally, Molecular Docking was methodically carried out with PyRx and BIOVIA discovery studio to ascertain the binding affinities between drugs and proteins. Results: We recognised 23 DEThRGs, revealed that their primary areas of enrichment were immunomodulation and inflammatory response. Additionally, there are 8 hub genes and (BRD7 and CCAR1) were up regulated genes, while (HOXA6, CTBP2, HOXA3, HOXA5, CTBP1 and NCOR1) were down regulated genes. Furthermore, the drug–gene interaction network encompassed fifteen possible therapeutic agents that target proteins; molecular docking revealed that Azacitidine or Ivosidenib has highest binding affinity with all the 8 proteins. Conclusion: These compounds may have a significant impact on CSU development and may even serve as biomarkers for the CSU. Additional research on the medication is possible for clinical trials and therapeutic applications. The identification of eight pivotal genes associated with CSU presents fresh perspectives, potentially serving as pivotal indicators for diagnosis and novel therapeutic approaches.
Keywords: Bioinformatics; Biomarker; Chronic Spontaneous Urticaria (CSU); GEO; Hub genes; Immunology; Th-related genes; differentially expressed genes; inflammation